Gradient methods with selection technique for the multiple-sets split feasibility problem - Yao, Yonghong; Postolache, Mihai; Zhu, Zhichuan (Optimization, 2020)
In this paper, we present two new iterative algorithms for approximating a solution of the multiple-sets split feasibility problem. The suggested algorithms are based on the gradient method with selection technique. Weak and strong convergence theorems are demonstrated.